2011
DOI: 10.1684/ecn.2011.0270
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) abundance correlates with p53 and Bcl-2 accumulation and patient age in a small cohort of North African nasopharyngeal carcinoma patients

Abstract: In North Africa, nasopharyngeal carcinoma (NPC) is characterized by a bimodal distribution involving a juvenile (≤ 30 years old) and an elder population (>30 years old). The Epstein Barr virus oncogene LMP1, the anti-apoptotic Bcl-2 protein and the tumor suppressor p53 have recently emerged as biomarkers of the disease. EGFR/ErbB1 expression is detected in the majority of NPC tumors with advanced disease. To obtain greater insight into the potential oncogenic mechanisms specific to these two NPC populations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…p53 has been reported to have at close relationship with human tumors, and functions to block cell cycle, inhibit cell proliferation, induce cell differentiation, initiate apoptosis and maintain the stability of genome (16). In the present study, higher concentrations of oxymatrine treatment (6 and 8 mg/ml) significantly induced the protein expression of p53 in NPC HK-1 cells.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…p53 has been reported to have at close relationship with human tumors, and functions to block cell cycle, inhibit cell proliferation, induce cell differentiation, initiate apoptosis and maintain the stability of genome (16). In the present study, higher concentrations of oxymatrine treatment (6 and 8 mg/ml) significantly induced the protein expression of p53 in NPC HK-1 cells.…”
Section: Discussionsupporting
confidence: 52%
“…Bcl2 is an apoptosis-regulator that has been thoroughly studied, and its change in expression not only affects normal apoptosis of damaged DNA cells and abnormal cells, but also the apoptosis of tumor cells (16). Bcl2 proteins are highly expressed in NPC tissues and atypical hyperplasia epithelium, which suggested that Bcl2 proteins may serve an important role in the early stage of NPC, and the overexpression of Bcl2 may also be related to the inhibition of the apoptosis of NPC (17).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR (epidermal growth factor receptor) is involved in many pathways related to cancer in vivo The most common way is that it could activate the Ras protein by dimerization and lead to the phosphorylation cascade and then stimulate the PI3K/Akt signaling pathway (Ono and Kuwano 2006). It has been proved that the expressions and functions of EGFR have abnormities in several kinds of human tumor issues and tumor cell lines (Bourouba 2011;Hwangbo 2013). Data presented in Shan et al (2014) demonstrated that low dose of AA was able to increase the proliferation of HepG2 cells through up-regulating EGFR expression.…”
Section: A B Cmentioning
confidence: 99%
“…Western blotting and real-time PCR showed that this may reflect an inhibitory effect of miR-141 on expression of bcl-2 (Fig. 4C-F), a downstream EGFR effector [9].…”
Section: Resultsmentioning
confidence: 99%